The EFFECT OF RESTING TIME AND BODY WEIGHT DIFFERENCES ON THE PHYSIOLOGICAL RESPONSE OF CHICKENS BEFORE SLAUGHTER PE - Sahranisa, Agisliani; Siagian, Tetty Barunawati (Universitas Djuanda, 2025)
Transportation of chickens to the slaughterhouse causes severe stress. This stress affects body temperature, respiratory rate, and body weight. Providing rest time before slaughter can reduce the negative impact of stress, restore physiological conditions, and result in good carcass quality. This study was conducted from August to November 2024 at the Cicurug Slaughterhouse. The study used broiler chickens weighing >1.5 kg and <1.5 kg, with 72 chickens in each group. The treatments included resting times of 60 minutes and 120 minutes. The parameters measured were physiological responses, including body temperature, respiratory rate, and body weight loss. Data were analyzed using a two-way ANOVA. The results showed three hypotheses: resting time affected body temperature (Sig.<0.05), body weight group did not affect body temperature (Sig.>0.05), and the interaction between resting time and body weight group affected body temperature (Sig.<0.05). Resting time did not affect respiratory rate (P>0.05), body weight group affected respiratory rate (Sig.<0.05), and the interaction between resting time and body weight group did not affect respiratory rate (Sig.>0.05). Resting time did not affect body weight loss (Sig.>0.05), body weight group affected body weight loss (Sig.<0.05), and the interaction between resting time and body weight group did not affect body weight loss (Sig.>0.05). Providing rest time for chickens that have just arrived at the slaughterhouse influences a decrease in body temperature, but has no effect on the decrease in respiratory rate and body weight loss.